2013
DOI: 10.1080/13658816.2013.802794
|View full text |Cite
|
Sign up to set email alerts
|

Automatic drainage pattern recognition in river networks

Abstract: In both GIS and terrain analysis, drainage systems are important components. Owing to local topography and subsurface geology, a drainage system achieves a particular drainage pattern based on the form and texture of its network of stream channels and tributaries. Although research has been done on the description of drainage patterns in geography and hydrology, automatic drainage pattern recognition in river networks is not well developed. This paper introduces a new method for automatic classification of dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…For example, the predicate "α is acute" will return a value equal or close to 1 if the angle α is small, and a value equal or close to 0 when α is large. Each pattern is characterized by a combination of predicates defined by IF-THEN rules: [14] showed that the method can classify drainages correctly with a few that remain unclassified. From their research, the classification is also robust as an alteration of MF parameters has a limited impact on the result.…”
Section: Catchment Elongation (δ)mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the predicate "α is acute" will return a value equal or close to 1 if the angle α is small, and a value equal or close to 0 when α is large. Each pattern is characterized by a combination of predicates defined by IF-THEN rules: [14] showed that the method can classify drainages correctly with a few that remain unclassified. From their research, the classification is also robust as an alteration of MF parameters has a limited impact on the result.…”
Section: Catchment Elongation (δ)mentioning
confidence: 99%
“…They relate to the junction angle between streams, the shape of tributaries and the networks. Zhang and Guilbert [14] use four different indicators to characterize the four drainage patterns presented in Figure 1: the average junction angle (α), the bent tributaries percentage (β), the average length ratio (γ) and the catchment elongation (δ) ( Table 1). …”
Section: Indicator Description Illustrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the evaluation presented below, we extend the topography analysis routines of previous investigators [37]- [39] to evaluate the feasibility of differentiating between geologic units and the extent to which the degree of fracture density can be interpreted from an integrated analysis of topographic parameters and drainage patterns. Figure 1 illustrates the differences between the drainage pattern for "soft" rock (alluvium) and "hard" Figure 1.…”
Section: Introductionmentioning
confidence: 99%